Cloning of ε‐poly‐L‐lysine (ε‐PL) synthetase gene from a newly isolated ε‐PL‐producing Streptomyces albulus NK660 and its heterologous expression in Streptomyces lividans. Issue 2 (14th January 2014) - Geng, Weitao; Yang, Chao; Gu, Yanyan; Liu, Ruihua; Guo, Wenbin; Wang, Xiaomeng; Song, Cunjiang; Wang, Shufang
Summary ε‐Poly‐L‐lysine (ε‐PL), showing a wide range of antimicrobial activity, is now industrially produced as a food additive by a fermentation process. A new strain capable of producing ε‐PL was isolated from a soil sample collected from Gutian, Fujian Province, China. Based on its morphological and biochemical features and phylogenetic similarity with 16S rRNA gene, the strain was identified as Streptomyces albulus and named NK660. The yield of ε‐PL in 30 l fed‐batch fermentation with pH control was 4.2 g l−1 when using glycerol as the carbon source. The structure of ε‐PL was determined by nuclear magnetic resonance (NMR) and matrix‐assisted laser desorption/ionization–time of flight mass spectrometry (MALDI‐TOF MS). Previous studies have shown that the antimicrobial activity of ε‐PL is dependent on its molecular size. In this study, the polymerization degree of the ε‐PL produced by strain NK660 ranged from 19 to 33 L‐lysine monomers, with the main component consisting of 24–30 L‐lysine monomers, which implied that the ε‐PL might have higher antimicrobial activity. Furthermore, the ε‐PL synthetase gene (pls) was cloned from strain NK660 by genome walking. The pls gene with its native promoter was heterologously expressed in Streptomyces lividans ZX7, and the recombinant strain was capable of synthesizing ε‐PL. Here, we demonstrated for the first time heterologous expression of the pls gene in S. lividans. The heterologous expression of pls gene in S. lividans will open new avenues for elucidating the molecular mechanisms of ε‐PL synthesis.